Exploding Offers and Buy-Now Discounts. - Armstrong, M; Zhou, J (Department of Economics (University of Oxford), 2011)
A common sales tactic is for a seller to encourage a potential customer to make her purchase decision quickly, before she can investigate rival deals in the market. We consider a market with sequential consumer search in which firms can achieve this either by making an exploding offer (which permits no return once the consumer leaves) or by offering a buy-now discount (which makes the price paid for immediate purchase lower than the regular price). We show that firms often have an incentive to use these sales techniques, regardless of their ability to commit to their selling policy. We examine the impact of these sales techniques on market performance. Inducing consumers to buy quickly not only reduces the quality of the match between consumers and products, but may also raise market prices.